2022
DOI: 10.1590/1806-9282.20210771
|View full text |Cite
|
Sign up to set email alerts
|

Do biomarkers have predictive value in the treatment modality of the patients diagnosed with bowel obstruction?

Abstract: OBJECTIVES: This study aimed to investigate the ability of the biomarkers to predict the surgery treatment and mortality in patients above 18 years of age who were hospitalized with the diagnosis of bowel obstruction from the emergency department.METHODS: This is a 2-year retrospective study. The patients' demographic data, laboratory parameters on admission to emergency department, treatment modalities, and the length of hospital stay were recorded. Patients were divided into two groups: conservative and surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(21 reference statements)
2
1
0
Order By: Relevance
“…A review of the studies in the relevant literature revealed that high CRP levels were correlated with the duration of hospitalization and were a predictive factor in determining in-hospital mortality. [15,16] In the present study, high CRP was associated with mortality, consistent with the literature. Yoon and Lee reported that high neutrophil levels were predictive factors in determining in-hospital mortality, whereas lymphocyte levels were not effective in predicting mortality in the same study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A review of the studies in the relevant literature revealed that high CRP levels were correlated with the duration of hospitalization and were a predictive factor in determining in-hospital mortality. [15,16] In the present study, high CRP was associated with mortality, consistent with the literature. Yoon and Lee reported that high neutrophil levels were predictive factors in determining in-hospital mortality, whereas lymphocyte levels were not effective in predicting mortality in the same study.…”
Section: Discussionsupporting
confidence: 92%
“…Studies performed on patients who underwent surgery for small bowel obstruction showed that low albumin levels were correlated with the duration of hospitalization and were a risk factor for mortality. [16,17] In the present study, an association between low albumin levels and mortality was identified. In addition, this is possibly the first study to evaluate the relationship between HALP score and mortality in patients with ileus.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation